Pengaruh Strategi Pembelajaran Everyone Is A Teacher Here Terhadap Pemahaman Fiqih Kelas VIII di MTs Perguruan Mu'allimat Cukir Jombang - Chamidatus Sholichah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Everyone is a teacher. Here's a learning strategy for understanding fiqih in Mu'allimat Cukir Jombang College MTs. Learning this strategy teaches how a student is capable and can re-explain the material learned to the subject. The objective of this study is to learn: 1) To learn about learning strategies Everyone Is A Teacher Here in Fiqih Understanding and to understand the influence of the Everyone Is A Teacher Here strategy on the understanding of Fiqih Class VIII in MTs Mu’allimat College. This research uses a quantitative approach. This research uses quantitative methods with the type of ex post facto research. As for the population and samples taken from 35 students in the eighth grade, data sampling in this study uses angle spreads and tests. Data analysis techniques use simple linear regression tests. The results of the study can be concluded as follows: 1) From the results of the research, it can be seen that the average learning score of students using learning strategies from Everyone Is A Teacher Here reached 52.06. 2) Understanding Fiqih grade VIII in MTs Mu’allimat Cukir Jombang is in the category of quite well seen, as the average understanding Fiqih student grade VIII reached 21.91. 3) the influence of learning strategies Everyone is a teacher here. Understanding Fiqih Class VIII at MTs Mo’allimate is a quite good learning strategy. Everyone is a teacher here, influenced by understanding the fiqhi class VIII in Mu’alimat Ccur Jombing MTs. Based on the T-test with a significance value of 0.005 < 0.05. The t-count value on the X variable is 0.431>0.005 (nilai t-tabel X).